Prevalence And Risk Factors Of Hypertension Among Adults Attending Family Medicine Clinics (The Review of Diabetic Studies, 2025)
Background: Hypertension is a prevalent chronic condition with significant public health implications, particularly in primary care settings where early detection and management are critical. Family medicine clinics serve as key access points for diverse adult populations, yet the burden and determinants of hypertension in these settings require further characterization to inform targeted interventions.Methods: A cross-sectional study was conducted among 420 adults attending family medicine clinics. Data were collected using a structured questionnaire, and blood pressure was measured using a calibrated sphygmomanometer. Sociodemographic, lifestyle, and clinical characteristics were assessed. Descriptive statistics, chi-square tests, and multivariable logistic regression were used to analyze the prevalence of hypertension and its associated risk factors.Results: The overall prevalence of hypertension was 43.8%. Hypertension was significantly higher in older age groups, with the highest prevalence (69.0%) observed among those aged ≥60 years. Key risk factors included obesity (adjusted odds ratio [AOR] = 2.76), high dietary salt intake (AOR = 2.14), physical inactivity (AOR = 1.98), and a family history of hypertension (AOR = 1.87). Smoking and overweight were also significantly associated with hypertension in bivariate analyses.Conclusion: Hypertension is highly prevalent among adults attending family medicine clinics, with modifiable lifestyle factors and genetic predisposition playing important roles. These findings underscore the need for integrated primary care strategies that emphasize lifestyle modification, regular screening, and sustained patient follow-up to reduce the burden of hypertension and its complications.